Cyclosporine-Induced Kaposi Sarcoma in a Patient With Ulcerative Colitis. Issue 5 (26th May 2021) - Clarke, Lindsay M.; Chawla, Karan; Tabbara, Nadeem; Szvarca, Daniel; Stachura, Anna; Theisen, Brian; Chandler, Matthew; Borum, Marie L.
ABSTRACT: Kaposi sarcoma (KS) is an angioproliferative neoplasm associated with human herpesvirus-8. Gastrointestinal KS has been well documented in immunosuppressed solid organ transplant patients, with only 26 iatrogenic cases published in patients with inflammatory bowel disease. We report a 24-year-old patient with ulcerative colitis, maintained on cyclosporine for 2 years, who presented with watery, nonbloody diarrhea and weight loss. Colonoscopy revealed human herpesvirus-8-positive hemorrhagic nodules throughout the colon and terminal ileum, with diffuse lymphadenopathy on computed tomography consistent with KS. As gastrointestinal KS may present with symptoms that mimic inflammatory bowel disease, it is critical to maintain suspicion in patients on prolonged immunosuppression to reduce complications.